1970
DOI: 10.1002/jbm.820040310
|View full text |Cite
|
Sign up to set email alerts
|

The role of organics in metallic passivation

Abstract: SummaryOrganic substances are known to affect, electrochemical reactions. The passivation characteristics of iron have been shown tc? be drastically altered in the presence of certain ions. Since passivation mnst occur to preserve the physical integrity of some materials in viuo, a study was init,iated to determine the effect of alanine, bovine plasma albumin, and cyst,ine on t,his phenomenon for nickel and copper.The procedure was as follows: ( 1 ) potential pH diagrams which show stable metal-containing form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In our previous papers [15,16], we showed that the adsorption of BSA and b-LG onto an austenitic stainless steel surface enhances the dissolution of the passive oxide film on the surface, thus increasing corrosion of the alloy. Svare et al [23] showed that horse serum affects the dissolution of Ni, which is one of the major components of austenitic stainless steels. Williams et al [24] found that 316L stainless steel exhibited greater corrosion in the presence of serum proteins while Woodman et al [25] have found that the predominant corrosion products from 316L stainless steel were organometallic complexes with serum proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous papers [15,16], we showed that the adsorption of BSA and b-LG onto an austenitic stainless steel surface enhances the dissolution of the passive oxide film on the surface, thus increasing corrosion of the alloy. Svare et al [23] showed that horse serum affects the dissolution of Ni, which is one of the major components of austenitic stainless steels. Williams et al [24] found that 316L stainless steel exhibited greater corrosion in the presence of serum proteins while Woodman et al [25] have found that the predominant corrosion products from 316L stainless steel were organometallic complexes with serum proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial corrosion also represents a large problem, and therefore studies [15,16,[23][24][25][26] have been made to evaluate the effect of proteins on the corrosion of metallic materials such as stainless steel typically used in the food and pharmaceutical industries and in medicine. It was generally established that proteins interact and alter the corrosion behaviour of metallic materials in two ways: adsorption and chelation.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper (14), we showed that the adsorption of bovine serum albumin (BSA) onto an austenitic stainless steel surface enhances the dissolution of the passive oxide film on the surface, thus increasing corrosion of the alloy. Svare et al (18) showed that horse serum effected the dissolution of Ni, which is one of the major components of austenitic stainless steels. Williams et al (22) found that 316L stainless steel exhibited greater corrosion in the presence of serum proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the overall costs of cleaning are very high. A large number of investigations to better understand the process of fouling have been reported (17)(18)(19), but a real breakthrough in the complete control of fouling has not been reached. This is mainly due to the complexity of the dairy systems and a lack of understanding of the mechanism of fouling.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Svare showed that specific amino acids could influence alloy passivation: for cysteine in Ringer's the passivation of Cu was improved, but alanine and albumin had little or no effect. [17] Therefore, interaction of metallic materials and protein composition, especially the enzymes in saliva, and their consecutive influences on corrosion need more research.…”
Section: Introductionmentioning
confidence: 99%